2018
DOI: 10.1111/vru.12674
|View full text |Cite
|
Sign up to set email alerts
|

High field magnetic resonance imaging is comparable with gross anatomy for description of the normal appearance of soft tissues in the equine stifle

Abstract: High field magnetic resonance imaging (MRI) is increasingly used for horses with suspected stifle disease, however there is limited available information on normal imaging anatomy and potential incidental findings. The aim of this prospective, anatomic study was to develop an optimized high field MRI protocol for evaluation of the equine stifle and provide detailed descriptions of the normal MRI appearance of the stifle soft tissues, using ultrasound and gross pathological examination as comparison tests. Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Inclusion criteria were a minimum weight of 15 kg, the availability of information on the age, sex and breed and the absence of radiographic abnormalities (see further). The sample size was determined based on similar published research [52, 53]. The hind limbs were disarticulated in the coxofemoral joint within the first 24 h post mortem, with the cadavers stored at 7 °C and all procedures performed within 60 h post mortem.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were a minimum weight of 15 kg, the availability of information on the age, sex and breed and the absence of radiographic abnormalities (see further). The sample size was determined based on similar published research [52, 53]. The hind limbs were disarticulated in the coxofemoral joint within the first 24 h post mortem, with the cadavers stored at 7 °C and all procedures performed within 60 h post mortem.…”
Section: Methodsmentioning
confidence: 99%
“…Since MRI can supply clear information of the soft tissue structure without ionizing radiation, [ 45 ] we also investigated the MRI performance of ICG‐PtMGs@HGd using gadopentetic acid (Gd‐DTPA), [ 31,46 ] a clinically used MRI contrast agent, as the control. As expected, the in vitro T 1 ‐weight MR images showed that the MRI signals from both ICG‐PtMGs@HGd and Gd‐DTPA significantly increased with Gd concentration, and a linear correlation was found between the longitudinal relaxation rate (1/ T 1 ) of water protons and the concentration of Gd (III) (Figure S4a,b, Supporting Information), confirming the effective MRI performance of Gd (III).…”
Section: Resultsmentioning
confidence: 99%
“…The used sequences were extensive in every plane so that an optimal protocol could be determined. Under clinical Magnetic resonance imaging is frequently used in horses owing to its ability to produce high-contrast and anatomically detailed tomographic images [9,22]. The use of MRI in camels is still in its infancy and was limited to cadaveric studies.…”
Section: Discussionmentioning
confidence: 99%
“…By knowing the variation in MRI images in the normal camel, it would be possible to understand the importance of signal intensity changes in the clinical patients. Additionally, description of the high field MRI appearance of the tarsal joint structures can also be useful in the interpretation of radiographs, ultrasound, and computed tomography of the camel tarsus [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation